The Chilean burden of disability-adjusted life years due to cardiovascular diseases: Results from the Global Burden of Disease Study 2021 - Camilo Briones-Valdivieso; Claudia Nuñez; Andrés Celis; Jaqueline Araneda; Carlos Cristi-Montero; Gary O’Donovan; Carlos Celis-Morales; Salil V. Deo; Fanny Petermann-Rocha (PLoS ONE, 2025)
Cardiovascular disease (CVD) remains a leading cause of death and disability worldwide, including Chile. While mortality rates from CVD are well-documented, the associated burden of disability-adjusted life years (DALYs) and the impact of key modifiable risk factors have yet to be fully explored. This study aims to describe the temporal trends of CVD-related DALYs in Chile, stratified by gender, and to identify the primary risk factors contributing to this burden. An ecological study was conducted using data from the Global Burden of Disease Study 2021. We analysed age-standardised DALYs rates for overall and specific CVDs in Chile from 1990 to 2021. For the year 2021, we calculated the percentage distribution of DALYs by CVD type. Where applicable, CVDs were examined in relation to behavioural, metabolic, and environmental risk factors, and relative changes in DALYs over time. Over the last three decades, the overall CVD DALYs rate in Chile decreased substantially. Ischaemic heart disease and stroke accounted for most of the CVD burden, with gender differences observed. Stroke predominated in females and ischaemic heart disease in males. Metabolic risk factors, particularly high systolic blood pressure (SBP), were the most significant contributors to CVD DALYs, followed by behavioural and environmental risk factors. Although the rates of CVD DALYs have declined significantly in Chile during the past three decades, the burden remains substantial and with gender-specific differences. Metabolic risk factors, especially high SBP, followed by behavioural and environmental factors, remain key contributors to CVD, highlighting the need for continued public health efforts focused on multi-level interventions to reduce the impact of these risk factors on cardiovascular health, such as adopting lower blood pressure goals among older people.